Problems and Challenges of Science Learning Curriculum in Indonesia: A Systematic Literature Review and Bibliometric Analysis - Nadia Nuri Silmiah; Chaerul Rochman; Adam Malik; Tri Wahyu Agustina; Nurdin (IAIN Sorong, 2025)
Curriculum changes that adapt to current developments often create new obstacles in the implementation of learning. This study aims to analyze the problems and challenges in the implementation of the Natural Sciences (IPA) curriculum in Indonesia through the Systematic Literature Review (SLR) method and bibliometric analysis. Twenty-three scientific articles published between 2021 and 2025 were analyzed using the Publish or Perish (PoP) tool for bibliographic data collection and VOSviewer for research network map visualization. The analysis results show a significant increase in publications from 2024 to 2025, indicating that the Independent Curriculum topic is currently a primary focus of science education research. Keyword mapping resulted in three main clusters: difficulties for teachers and students in understanding and implementing Independent Curriculum-based science learning, challenges in implementing the Independent Curriculum and the role of science teachers, and contextual issues such as limited facilities, low scientific literacy, and the integration of local wisdom. The study also identified a research gap regarding the effectiveness of the Independent Curriculum in improving science literacy and student character. Therefore, improving teacher curriculum literacy, cross-institutional research collaboration, and strengthening science learning based on technology and local wisdom are needed to achieve contextual and modern learning.